2021
DOI: 10.3390/j4020014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Hygiene Behaviours among In-School Adolescents in Ghana

Abstract: (1) Background: Despite a global call to act to resolve communicable diseases caused by lack of clean water, sanitation, and hygiene, many people in low- and middle-income countries continue to die each year. In this study, we looked at in-school adolescents’ oral and hand hygiene activities in Ghana, as well as the factors that influence them. (2) Methods: This was a cross-sectional study that utilised data on 1348 in-school adolescents from the 2012 global school-based health survey. Using Stata software ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
2
1
1
Order By: Relevance
“…Nearly 36% of Mongolian school-aged adolescents had poor oral hygiene seemed almost the same as the previous study [18]. In addition, this result was also higher than Indonesia in 2015 (10.8%) [19], Suriname in 2016 (14.3%), and Trinidad and Tobago in 2017 (22.1%) [20], but lower than Ghana in 2012 (37.4%) [12].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Nearly 36% of Mongolian school-aged adolescents had poor oral hygiene seemed almost the same as the previous study [18]. In addition, this result was also higher than Indonesia in 2015 (10.8%) [19], Suriname in 2016 (14.3%), and Trinidad and Tobago in 2017 (22.1%) [20], but lower than Ghana in 2012 (37.4%) [12].…”
Section: Discussionsupporting
confidence: 79%
“…In six Southeast Asian countries, the results showed that 17.1% had poor oral hygiene (brushing teeth less than twice a day) [7], whereas in Indonesia 10.8% had poor oral hygiene according to the GSHS (Global School-based Health Survey) in 2014-2015 [8]. Poor oral hygiene among adolescents has been associated with being male [9], older age or grade [10], hand hygiene behaviors [11], mental distress including being bullied and lonely [12], smoking and alcohol consumption [13], and health risk behaviors such as inadequate exercise and sedentary leisure time behavior [7].…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to higher LUP, the knowledge of children, and the fact that the residence was only in town. But the result was the same as a similar study done in Mereb-Leke District (61.2%) (11) and 62.6% in Ghana (20). The overall personal hygiene knowledge of students was 278 (52.2%), which was higher than the survey study (32.11%) in Rural Students from Five Western Provinces in China (21).…”
Section: Discussionsupporting
confidence: 75%
“…However, among primary school students in Fiche town, the good OHP was 55.2%. This practice was small compared with a similar study, 79.9% in Ghana (20) and 70.4% in Manipur, North Eastern India (33); it was the same as 54.5% in Southeast Serbia (34). This difference may be due to family educational status and the small sample size Almost half of the 284 (53.2%) students were brushing their teeth once daily; 147 (27.5%) brushed twice, and 40 (7.5%) brushed three times or more per day.…”
Section: Discussioncontrasting
confidence: 73%